Multicenter analysis of body mass index, lung function, and sputum microbiology in primary ciliary dyskinesia. Issue 12 (13th January 2014) - Maglione, Marco; Bush, Andrew; Nielsen, Kim G.; Hogg, Claire; Montella, Silvia; Marthin, June K.; Di Giorgio, Angela; Santamaria, Francesca
Summary Background No studies longitudinally, simultaneously assessed body mass index (BMI) and spirometry in primary ciliary dyskinesia (PCD). Methods We determined BMI and spirometry in 158 PCD children and adolescents from London, UK (n = 75), Naples, Italy (n = 23) and Copenhagen, Denmark (n = 60) at first presentation and during follow‐up. Annual BMI and spirometry were prospectively collected and analyzed over blocks of 2, 4, and 6 consecutive years. Sputum pathogens were recorded. Results Age at first spirometry was 8.7 years (range, 4.2–17.4). Mean Z scores of first measured BMI, FEV1, FVC, and FEF25–75 were 0.01, −1.37, −0.84, and −1.68, respectively. First spirometry was not more frequently impaired in patients referred at age ≥6 years than in those referred at preschool age (P = 0.13). There were no differences in slopes for BMI, FEV1, FVC, or FEF25–75 over any time block. H. influenzae was the most common pathogen, isolated at least once in 65% of patients. P. aeruginosa was found in 58 subjects (37%) of whom 8 (5%) were chronically infected. Neither pathogens was associated with spirometry changes. Conclusions Preschool referral to a PCD center was not associated with better spirometry or BMI. PCD children and adolescents receiving centralized care show steady BMI and spirometry during medium term follow‐up. There was a high prevalence of Pseudomonas aeruginosa infection, but the evolution of spirometry or BMI was not affected by this microorganism in medium term. Despite our longitudinal analysis showed no differences between the three centers, the assessment of spirometry and BMI over time represents a quality improvement tool. Future studies are needed to highlight the role of spirometry and BMI in long term PCD management and identify subgroups of patients with a higher risk of early lung failure or nutritional problems. Pediatr Pulmonol. 2014; 49:1243–1250. © 2014 Wiley Periodicals, Inc.